2012
DOI: 10.1007/s11655-012-1121-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pien Tze Huang (片仔癀) on angiogenesis in vivo and in vitro

Abstract: PZH could inhibit angiogenesis in vivo in CAM model and in vitro on HUVECs, suggesting that inhibiting tumor angiogenesis might be one of the mechanisms by which PZH treats cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…Modern pharmacological studies have proposed that PZH not only exhibits therapeutic effects on hepatocellular carcinoma and CRC in clinical trials (13,14), but also inhibits the growth of human colon carcinoma cells by activating mitochondrion-dependent apoptosis (15). Moreover, PZH reportedly suppressed the cell proliferation and tumor angiogenesis of CRC carcinoma cells in vitro and in vivo (16,17). To elucidate further the antitumor mechanism of action of PZH, we evaluated its efficacy against tumor invasiveness in vivo and in vitro and investigated its underlying molecular mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Modern pharmacological studies have proposed that PZH not only exhibits therapeutic effects on hepatocellular carcinoma and CRC in clinical trials (13,14), but also inhibits the growth of human colon carcinoma cells by activating mitochondrion-dependent apoptosis (15). Moreover, PZH reportedly suppressed the cell proliferation and tumor angiogenesis of CRC carcinoma cells in vitro and in vivo (16,17). To elucidate further the antitumor mechanism of action of PZH, we evaluated its efficacy against tumor invasiveness in vivo and in vitro and investigated its underlying molecular mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, Migration assays. Migration ability of the CRC cell lines was evaluated by wound-healing, as previously described (15). Briefly, CRC cells were seeded into 6-well plates (10 6 cells/well in 2 ml culture medium).…”
Section: Detection Of Apoptosismentioning
confidence: 99%
“…In fact, PZH has long been used as an alternative treatment strategy for cancers in China and Southeast Asia. Previously, we reported that PZH can inhibit CRC growth in vivo and in vitro via promotion of apoptosis and suppression of proliferation of cancer stem cells (CSCs) as well as inhibition of angiogenesis and reversal of multidrug resistance through multiple pathways while causing minimal side-effects (13)(14)(15)(16)(17). Recently, we found that PZH also prevents metastasis by inhibiting the progression of epithelial-mesenchymal transition (EMT) (18,19), but the underlying mechanism of the antimetastasis effects of PZH are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…PZH a well-known traditional Chinese formula, first prescribed 450 years ago in the Ming Dynasty, has long been used in China for cancer treatment (22)(23)(24). Although it has been shown that PZH inhibits colon cancer growth via the induction of apoptosis and inhibition of tumor angiogenesis (26)(27)(28), the precise mechanism of its anticancer effect remains largely unclear. Therefore, in order for PZH to be developed further as an anticancer agent, its underlying molecular mechanism of action should be elucidated.…”
Section: Pzh Regulates the Expression Of Cyclin D1 And Cdk4 Inmentioning
confidence: 99%
“…In addition, in experimental animals PZH inhibits the growth of Ehrlich-Ascites tumor, gastric carcinoma, and hepatoma (25). Moreover, we recently reported that PZH is able to inhibit colon cancer growth both in vivo and in vitro via the promotion of apoptosis and inhibition of tumor angiogenesis (26)(27)(28) we evaluated its effect on the proliferation of the human colon carcinoma cell line Caco-2 and investigated the underlying molecular mechanism. Cell culture.…”
Section: Introductionmentioning
confidence: 99%